2008
DOI: 10.1590/s0101-98802008000300001
|View full text |Cite
|
Sign up to set email alerts
|

Resultados do tratamento do câncer colorretal (T4) perfurado: análise de 14 pacientes operados

Abstract: INTRODUÇÃOA perfuração neoplásica no câncer colorretal é uma complicação incomum que envolve um quadro dramático que invariavelmente evolui para intervenção cirúrgica imediata. Nessa situação, tanto a morbidade quanto a mortalidade são extremamente elevadas, em virtude principalmente do quadro clínico de peritonite fecal que se instala (1-3). Índices de mortalidade pós-operatória de 11 até 43 % têm sido descritos, mesmo em casuísticas mais recentemente publicadas (1,3,(4)(5)(6)(7). Não se trata de uma circunst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Symptoms of CRC can be nonspecific or quite fulminant [40]. Emergency situations are most commonly related to the complications of tumour obstruction [41] or tumour perforation [41,42]; these are relatively rare complications, both with a poor prognosis and high risk of recurrence [41]. In a meta-analysis, Jellema et al analysed various symptoms of CRC and concluded that the symptoms most commonly investigated included abdominal pain, rectal bleeding, change in bowel habits, and perianal symptoms.…”
Section: Symptomsmentioning
confidence: 99%
“…Symptoms of CRC can be nonspecific or quite fulminant [40]. Emergency situations are most commonly related to the complications of tumour obstruction [41] or tumour perforation [41,42]; these are relatively rare complications, both with a poor prognosis and high risk of recurrence [41]. In a meta-analysis, Jellema et al analysed various symptoms of CRC and concluded that the symptoms most commonly investigated included abdominal pain, rectal bleeding, change in bowel habits, and perianal symptoms.…”
Section: Symptomsmentioning
confidence: 99%